2004
DOI: 10.3354/dao060065
|View full text |Cite
|
Sign up to set email alerts
|

18S ribosomal DNA-based PCR identification of Neoparamoeba pemaquidensis, the agent of amoebic gill disease in sea-farmed salmonids

Abstract: Neoparamoeba pemaquidensis is a parasomal amoeboid protozoan identified as the agent of amoebic gill disease (AGD) in Atlantic salmon Salmo salar reared in sea-pens in Tasmania, Australia, and coho salmon Oncorhynchus kisutch farmed on the west coast of the USA. Outbreaks of AGD caused by immunologically cross-reactive paramoebae have also been reported in seafarmed salmonids in several other countries. Complete 18S rDNA sequences were determined for respective paramoebae isolated from infected gills of salmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 29 publications
1
31
2
Order By: Relevance
“…Briefly, AGD had been maintained in this tank for several months, with introduced fish exhibiting gross signs of AGD within 3 d of cohabitation. The presence of Neoparamoeba pemaquidensis, the putative agent of AGD, was routinely confirmed using a modified indirect fluorescent antibody test (Roberts & Powell 2003b), PCR (Wong et al 2004), immunohistochemistry (Bridle et al 2003) and by visually identifying parasomes within isolated gill amoebae (Morrison et al 2004). All fish were fed to satiation daily with non-medicated pellets, and further lethally sampled 3 and 5 d into their cohabitation with AGD-affected fish.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, AGD had been maintained in this tank for several months, with introduced fish exhibiting gross signs of AGD within 3 d of cohabitation. The presence of Neoparamoeba pemaquidensis, the putative agent of AGD, was routinely confirmed using a modified indirect fluorescent antibody test (Roberts & Powell 2003b), PCR (Wong et al 2004), immunohistochemistry (Bridle et al 2003) and by visually identifying parasomes within isolated gill amoebae (Morrison et al 2004). All fish were fed to satiation daily with non-medicated pellets, and further lethally sampled 3 and 5 d into their cohabitation with AGD-affected fish.…”
Section: Methodsmentioning
confidence: 99%
“…Neoparamoeba sp. was identified among populations of amoebae based on the existence of a parasome, an endosymbiont (Dykov谩 et al 2003), reactivity with a polyclonal antibody visualised by an immunofluorescent antibody test (Howard & Carson 1993) and detection, via polymerase chain reaction (PCR), of small subunit (SSU) rDNA originally thought to be specific to N. pemaquidensis (Wong et al 2004) but subsequently also found capable of detecting N. branchiphila. Sites were designated positive if one or both duplicate sediment samples revealed the pres- Site reduction/oxidation (redox) potential and sulphide assessment.…”
Section: Methodsmentioning
confidence: 99%
“…Many authors assumed that Neoparamoeba pemaquidensis was the sole aetiological agent of AGD of Atlantic salmon (Douglas-Helders et al 2000, 2001a,b, 2002, 2003a,b,c, 2005, Adams & Nowak 2001, Munday et al 2001, Tan et al 2002, Clark et al 2003, Powell & Clark 2003, Bowman & Nowak 2004, Wong et al 2004, Zilberg 2005. However, the isolation of N. branchiphila from the gills of AGD-affected fish (Dykov谩 et al 2005) suggested that AGD may be a condition of mixed aetiology.…”
Section: Introductionmentioning
confidence: 99%